A novel POSS-coated quantum dot for biological application - Rizvi SB (Dove Medical Press, 2012)
Sarwat B Rizvi,1 Lara Yildirimer,1 Shirin Ghaderi,1 Bala Ramesh,1 Alexander M Seifalian,1,2 Mo Keshtgar1,21UCL Centre for Nanotechnology and Regenerative Medicine, Division of Surgery and Interventional Science, University College London, United Kingdom; 2Royal Free Hampstead NHS Trust Hospital, London, United KingdomAbstract: Quantum dots (QDs) are fluorescent semiconductor nanocrystals that have the potential for major advancements in the field of nanomedicine through their unique photophysical properties. They can potentially be used as fluorescent probes for various biomedical imaging applications, including cancer localization, detection of micrometastasis, image guided surgery, and targeted drug delivery. Their main limitation is toxicity, which requires a biologically compatible surface coating to shield the toxic core from the surrounding environment. However, this leads to an increase in QD size that may lead to problems of excretion and systemic sequestration. We describe a one pot synthesis, characterization, and in vitro cytotoxicity of a novel polyhedral oligomeric silsesquioxane (POSS)-coated CdTe-cored QD using mercaptosuccinic acid (MSA) and D-cysteine as stabilizing agents. Characterization was performed using transmission electron microscopy Fourier transform infrared spectroscopy, and photoluminescence studies. POSS-coated QDs demonstrated high colloidal stability and enhanced photostability on high degrees of ultraviolet (UV) excitation compared to QDs coated with MSA and D-cysteine alone (P value < 0.05). In vitro toxicity studies showed that both POSS and MSA-QDs were significantly less toxic than ionized salts of Cd+2 and Te-2. Confocal microscopy confirmed high brightness of POSS-QDs in cells at both 1 and 24 hours, indicating that these QDs are rapidly taken up by cells and remain photostable in a biological environment. We therefore conclude that a POSS coating confers biological compatibility, photostability, and colloidal stability while retaining the small size and unique photophysical properties of the QDs. The amphiphilic nature of the coating allows solubility in aqueous solutions and rapid transfer across cell membranes, enabling the use of lower concentrations of the QDs for an overall reduced toxicity particularly for prolonged live cell and in vivo imaging applications.Keywords: quantum dots, polyhedral oligomeric silsesquioxane, surface coating, cytotoxicity